What makes concept cartoons more effective? using research to inform practice [Kavram karikatürlerinin etkililiǧini nasil artirabiliriz? uygulamayi etkin kilma noktasinda araştirmadan yararlanma] - (:unkn) unknown (My University, 2009)
The purpose of the present study is to propose several ways of making concept cartoons more effective and to find out their effectiveness of concept cartoons on learning. Both case study and pre and post experimental research designs were used. The main data sources were written feedback form collected from the learners, field notes concerning classroom observations and videotape recordings of the instruction. Findings of the study indicated that concept cartoons in form of worksheets are as effective as posters in remedying students' misconceptions and helping them to understand scientific ideas. They also indicated that cartoon characters do not cause change in students' response pattern while minimizing classroom management problems during whole class reflection activity.
Keywords: Concept cartoon; Constructivism; Design; Science education; Teaching